Elucidating the role of nitrogen plasma composition in the low-temperature self-limiting growth of indium nitride thin films. Issue 46 (21st July 2020) - Ilhom, Saidjafarzoda; Mohammad, Adnan; Shukla, Deepa; Grasso, John; Willis, Brian G.; Okyay, Ali K.; Biyikli, Necmi
Abstract : Hollow-cathode plasma-generated hydrogen radicals induce crystal phase transformation from h-InN to c-In2 O3 during plasma-enhanced atomic layer deposition using trimethyl-indium and Ar/N2 plasma. Abstract : In this work, we have studied the role varying nitrogen plasma compositions play in the low-temperature plasma-assisted growth of indium nitride (InN) thin films. Films were deposited on Si (100) substrates using a plasma-enhanced atomic layer deposition (PE-ALD) reactor featuring a capacitively-coupled hollow-cathode plasma source. Trimethylindium (TMI) and variants of nitrogen plasma (N2 -only, Ar/N2, and Ar/N2 /H2 ) were used as the metal precursor and nitrogen co-reactant, respectively. In situ ellipsometry was employed to observe individual ligand exchange and plasma-assisted ligand removal events in real-time during the growth process. Only the samples grown under hydrogen-free nitrogen plasmas (Ar/N2 or N2 -only) resulted in nearly stoichiometric single-phase crystalline hexagonal InN (h-InN) films at substrate temperatures higher than 200 °C under 100 W rf-plasma power. Varying the plasma gas composition by adding H2 led to rather drastic microstructural changes resulting in a cubic phase oxide (c-In2 O3 ) film. Combining the in situ measured growth evolution with ex situ materials characterization, we propose a simplified model describing the possible surface reactions/groups during a unit PE-ALD cycle, which depicts the highly efficient oxygen incorporation in the presence of hydrogen radicals. Further structural, chemical, and optical characterization have been carried out on the optimal InN films grown with Ar/N2 plasma to extract film properties. Samples grown at lower substrate temperature (160 °C) and reduced/elevated rf-plasma power levels (50/150 W) displayed similar amorphous character, which is attributed to either insufficient surface energy or plasma-induced crystal damage. InN samples grown at 240 °C under 100 W rf-plasma showed clear polycrystalline h-InN layers with ∼20 nm average-sized single crystal domains exhibiting hexagonal symmetry.